An evaluation of dietary selenium nanoparticles for red sea bream (Pagrus major) aquaculture: growth, tissue bioaccumulation, and antioxidative responses - Mahmoud A.O. Dawood (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. Selenium nanoparticles (Se-NPs) were added at 0, 0.5, 1, and 2 mg per kg diet to assess its effects on the performance, Se bioaccumulation, blood health, and antioxidant status of red sea bream. After 45 days, Se-NPs positively impacted the growth and feed efficiency of red sea bream especially by 1 mg per kg diet. No significant (P > 0.05) changes in survival and somatic indices were noticed among groups. Dietary Se-NPs significantly (P < 0.05) increased the protein, lipid, and Se contents in the whole body, muscle, and liver tissues, whereas decreasing the whole-body moisture content of treated groups compared with the Se-NP-free group. Using of Se-NPs at 2 mg per kg diet resulted in the highest Se content in the complete body, muscle, and liver. Significantly enhanced intestine protease activity and hematocrit levels accompanied with low cholesterol and triglyceride were observed in fish fed Se-NP-enriched diets. Fish fed on Se-NPs at 0.5, 1, and 2 mg Se-NPs per kg diet exhibited significantly higher values of biological antioxidant potential than the control group (P < 0.05). Therefore, the obtained results recommends adding 1 mg Se-NPs per kg diet to improve the growth, feed efficiency, blood health, and antioxidant defense system of red sea bream.